The power of paradox : harness the energy of competing ideas to uncover radically innovative solutions - Schroeder-Saulnier, Deborah, 1959- (Career Press, 2014)
Should your company pursue global expansion or mine local opportunities? Take risks to grow dramatically or protect your current stability? Seek to maximize sales or the bottom line? We're so often faced with apparent paradoxes: continuity and change, conservatism and progressiveness, predictability and chaos. In business, inherent tensions are mistakenly viewed as problems to be resolved once the "correct" answer is found. But when we consider only one direction--either A or B--we only see part of the picture. The strongest and most innovative solutions are frequently realized not through either/or decisionmaking, but by pursuing two contrasting options at the same time. Taking readers through the same steps she's used to help Fortune 500 companies such as Scottrade, Georgia-Pacific, and Boeing, Deborah Schroeder-Saulnier reveals a dynamic critical-thinking process anyone can use to define the strategic tensions within his or her organization, identify the potential of seemingly conflicting options, and develop action steps to maximize the benefits of each. Complete with examples of companies that achieved a competitive advantage with this breakthrough strategy, The Power of Paradox will help you face chronic challenges with confidence and uncover unexpected and infinitely better solutions.--Publisher description.